The impact of impulse control disorders on cognitive decline in de novo Parkinson’s disease: a study based on structural MRI - Xu, Ruohong; Yang, Beisheng; Li, Juanling; Wei, Xiaofan; Zhang, Limin; Tian, Jiaqi; Zhang, Wei (Frontiers in Neurology, 2025)
BackgroundImpulse control disorders (ICDs) are common neuropsychiatric symptoms (NPS), which are prevalent among patients with Parkinson’s disease (PD). Current research has not clarified the impact of ICDs on cognitive function nor provided sufficient objective evidence. This study aims to explore the effects of ICDs on cognitive functions in PD patients, and further investigate associated cerebral structural changes.MethodsTwo hundred PD patients with normal cognition (PDNC) and 69 healthy controls were included from the Parkinson’s Progression Markers Initiative (PPMI), among these PDNC, 81 patients with “pure” ICDs (p-ICDs), 69 ICDs combined with other NPS (c-ICDs), and 50 patients without NPS. The cognitive status of each PD patient was obtained every year in four-year follow-up. The difference in conversion rates was obtained by chi-square test. Survival analysis was used to explore the conversion time difference among these groups. Further analysis was conducted on the potential structural difference. Finally, the correlation between significant brain structural changes and neuropsychological assessments were evaluated.ResultsThe survival analysis suggested that the conversion time of p-ICDs from normal cognition to MCI was significantly delayed compared to NPS-negative, with no significant difference relative to the c-ICDs. There is no significant difference in conversion rates among them. Morphological analysis revealed that compared to the NPS-negative group, the p-ICDs and c-ICDs groups exhibited thickness changes in certain regions (Bonferroni-corrected, p < 0.05).ConclusionOur findings suggest that ICDs might exert a protective effect against cognitive decline, potentially delay the occurrence of MCI in PDNC, which could be associated with alterations in cortical thickness.